Peran Pendidikan Islam Nonformal dalam Pengembangan Masyarakat Islam di Era Digital - Musttasir, Musttasir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2025)
The rapid development of information technology in the digital era has transformed nearly every aspect of society, including the system of non-formal Islamic education. Institutions such as majelis taklim (Islamic study circles), Qur’an Learning Centers (TPA), halaqah, and online study forums play a strategic role in shaping character and enhancing the religious literacy of Muslim communities. This article aims to analyze the role of non-formal Islamic education in the development of Muslim communities in the digital era, focusing on its opportunities, challenges, and relevant development models. The research adopts a descriptive qualitative approach through literature studies and the analysis of best practices from several non-formal Islamic educational institutions. The findings show that non-formal Islamic education in the digital era can expand the reach of da‘wah and learning, increase community participation, and strengthen Islamic values through the use of social media, online learning platforms, and technology-based applications. Nevertheless, challenges such as digital literacy gaps, limited human resources, and the need for regulation and quality standards remain unresolved issues. By effectively utilizing technology and building multi-stakeholder collaboration, non-formal Islamic education can transform into a driving force for the adaptive and sustainable development of Muslim communities in the digital age.